Who is Keeping Score? Estimating the Number of Foreign Workers in Malaysia - World Bank (World Bank, Malaysia, 2020)
Malaysia has experienced a rise in foreign labor inflows in response to steady economic expansion and demographic changes. The foreign workforce has been hovering around 15 percent of the total labor force in recent years according to Labour Force Surveys by the Department of Statistics Malaysia (DOSM). Foreign labor is concentrated in low-skilled occupations, and in Malaysia the term “foreign worker” specifically implies a foreigner doing low-skilled work. These foreign workers come from neighboring countries, predominantly Indonesia, Bangladesh, Nepal and the Philippines. This report is one of the first attempts, to team’s knowledge, to estimate the number of irregular foreign workers in Malaysia. Its contributions to this field are the following: first, it develops a conceptual framework that lays out potential entry points of irregular foreign workers. Second, it identifies alternative administrative data sources that could help estimate the magnitude of irregular foreign workers at each entry point. Third, it identifies methods that can be employed to measure irregular foreign workers with the current data availability and outlines what can be carried out further in the future using Immigration Department’s microdata. This report estimates the total number of foreign workers in Malaysiaranged from 2.96 million to 3.26 million in 2017. Among these, the number of irregular foreign workers is estimated to be 1.23 million – 1.46 million.